Research Needs in Flood Control: Metro Manila and Laguna Lake Region - Alejandrino, Angel A.; Coran, Samuel R.; Castro, Peter P. M. (Philippine Engineering Journal, 2021)
The perennial floods in Metro Manila and other towns in the Laguna Lake Region have been attributed to a number of factors. The need for a comprehensive research program is discussed in order to determine the degree of influence of these factors as they involve not only local but also regional considerations. The program includes development of the guidelines that would minimize the damaging effects of floods and would also rationalize the expenditures in coping with the flood problem.